Fibronectin Protects from Excessive Liver Fibrosis by Modulating the Availability of and Responsiveness of Stellate Cells to Active TGF-β - Kawelke, Nina; Vasel, Matthaeus; Sens, Carla; von Au, Anja; Dooley, Steven; Nakchbandi, Inaam A. (PLOS ONE, 2011)
Fibrotic tissue in the liver is mainly composed of collagen. Fibronectin, which is also present in fibrotic matrices, is required for collagen matrix assembly in vitro. It also modulates the amount of growth factors and their release from the matrix. We therefore examined the effects of the absence of fibronectin on the development of fibrosis in mice. Conditional deletion of fibronectin in the liver using the Mx promoter to drive cre expression resulted in increased collagen production and hence a more pronounced fibrosis in response to dimethylnitrosamine in mice. Exclusive deletion of fibronectin in hepatocytes or normalization of circulating fibronectin in Mx-cKO mice did not affect the development of fibrosis suggesting a role for fibronectin production by other liver cell types. The boosted fibrosis in fibronectin-deficient mice was associated with enhanced stellate cell activation and proliferation, elevated concentrations of active TGF-β, and increased TGF-β-mediated signaling. In vitro experiments revealed that collagen-type-I production by fibronectin-deficient hepatic stellate cells stimulated with TGF-β was more pronounced, and was associated with augmented Smad3-mediated signaling. Interfering with TGF-β signaling using SB431542 normalized collagen-type-I production in fibronectin-deficient hepatic stellate cells. Furthermore, precoating culture plates with fibronectin, but not collagen, or providing fibronectin fibrils unable to interact with RGD binding integrins via the RGD domain significantly diminished the amount of active TGF-β in fibronectin-deficient stellate cells and normalized collagen-type-I production in response to TGF-β stimulation. Thus, excessive stellate cell activation and production of collagen results from increased active TGF-β and TGF-β signaling in the absence of fibronectin. In conclusion, our data indicate that fibronectin controls the availability of active TGF-β in the injured liver, which impacts the severity of the resulting fibrosis. We therefore propose a novel role for locally produced fibronectin in protecting the liver from an excessive TGF-β-mediated response.